The Dynamics of Member Participation and Stakeholder Intervention In Women’s Empowerment Programs: A Study of The Ngudi Makmur and Bangun Sejahtera Women Farmers Groups - Salsabila Faiha’; Siti Fatonah; Luthfi Nurwafi Fatchurrohman (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The success of women's empowerment programs is determined not only by program design but also by the quality of member participation and the stakeholder interventions that support the implementation process. This study aims to examine the dynamics of member participation and stakeholder interventions in optimizing the implementation of women's empowerment programs within the Ngudi Makmur and Bangun Sejahtera Women's Farmer Groups (Kelompok Wanita Tani/KWT). The study uses a qualitative method with a descriptive approach, through data collection techniques such as in-depth interviews, observation, documentation, and literature review. Analysis of the research findings refers to Sherry Arnstein’s theory of participation ladder to identify the level of member participation at each stage of the empowerment process, the classification of forms of stakeholder intervention that affect the quality of participation and Naila Kabeer's empowerment theory to see the extent to which member participation contributes to women's empowerment outcomes. The findings indicate that differences in the level of members' participation across the program stages (planning, implementation, benefit utilization, and evaluation) were shaped by varying stakeholder interventions between the two groups that impact the distribution and the quality of benefits received by group members. Furthermore, the results show that the empowerment process extended beyond enhancing individual capacities to strengthening collective capacities, enabling members to become empowerment agents for other community groups. These findings suggest that improving the quality of women's participation is a key factor in maximizing the effectiveness and sustainability of women's empowerment programs.